STRATEGI DISEMINASI ASURANSI USAHA TERNAK SAPI/KERBAU KEPADA PETERNAK DI PROVINSI ACEH - Rahmat Fadhil; Allaily; Zikri Riefaldo HR (Jurnal Teknologi Industri Pertanian, 2022)
Cattle/buffalo business insurance (AUTS/K) is a government program to mitigate livestock businesses'risks, especially cattle and buffalo. For the participation and involvement of farmers in this program, it is necessaryto have a good dissemination process to be widely known, understood, and followed by the livestock businesscommunity throughout Indonesia. This study aimed to design a dissemination strategy for the AUTS/K using theSoft Systems Methodology (SSM) approach. This research was expected to produce a conceptual model of theAUTS/K dissemination so that the dissemination of information is comprehensive and evenly distributed to eacharea so that it can be accepted and applied by farmers. The AUTS/K dissemination strategy is a strategic plan togenerate innovation and creativity in disseminating information to farmers by utilizing various media. The resultsof the study will provide recommendations for AUTS/K dissemination strategies to improve and develop livestockinsurance by involving the government, religious and community leaders, insurance companies, extension agentsand field officers, universities and research institutions, as well as the use of advertising agencies and technologymedia in disseminating information to farmers in Aceh Province. In addition, the SSM approach can describeproblems well and form a conceptual for the dissemination model of AUTS/K in Aceh Province.Keywords: conceptual model, rich picture, soft systems methodology, livestock insurance, dissemination